Micro-Level Mechanisms to Support Value Co-Creation for Design of Digital Services - Tuunanen, Tuure; Lumivalo, Juuli; Vartiainen, Tero; Zhang, Yixin; Myers, Michael M. (SAGE Publications, 2023)
This study identifies micro-level value co-creation mechanisms that support the design of digital services. As services are now becoming digital—or at least digitally enabled—how to design digital services that enable value co-creation between a service provider and customers has become an increasingly important question. Our qualitative research study provides one answer to this question. Based on 113 in-depth laddering interviews analyzed using interpretive structural modeling, our study shows that value co-creation mechanisms differ between business-to-business and customer-to-customer digital service types. We identify five mechanisms to support value co-creation in the design of digital services: (1) Social use, (2) Customer orientation and decision making, (3) Service experience, (4) Service use context, and (5) Customer values and goals. We claim that firms can readily utilize these mechanisms to improve their customers’ service experiences.
Keywords: value co-creation; micro-level mechanisms; theory; design of digital services; qualitative research; laddering interview; interpretive structural modeling; fi=Tietojärjestelmätiede|en=Information Systems|